Etika dan Tantangan Dakwah dengan Artificial Intellegence - Nuha, achmad Arifulin (Dakwah, 2025)
Islamic preaching (dakwah) continues to evolve alongside advancements in digital technology, particularly through the utilization of Artificial Intelligence (AI). AI holds significant potential in supporting the dissemination of Islamic teachings via chatbots, automated fatwa systems, and AI-based religious learning applications. However, the implementation of AI in dakwah also faces various ethical challenges, including algorithmic bias, limitations in understanding complex religious contexts, and issues related to user data privacy and security. This study aims to analyze the role of AI in Islamic preaching, identify the challenges encountered, and explore ethical solutions for its implementation. Using a qualitative approach based on literature review, the research findings indicate that while AI enhances accessibility to religious information, it cannot replace scholars (ulama) in providing spiritual guidance and issuing fatwas that consider the social and cultural aspects of the Muslim community. Therefore, clear regulations and the involvement of Islamic scholars in AI development for dakwah are essential to ensure that this technology is used responsibly and aligns with Islamic values.